Mental Proofs of Prophecy in Tabsirat al-Adilla - ADYLCAN KYZY, Tolgonai (Scientific Journal of Faculty of Theology, 2020)
The headline of the article is mental proofs of prophecy in Tabsirat al-Adilla written by Abu’l Muin an- Nasafi, who was one of the most important persons in the Maturidi School, in the field of Kelam. The article goes on to share about opinions of scholars on the existence or non-existence of prophecy, about accepting the prophecy of Prophets by sane minds, about that mind is created and weak and also about feelings and mental proofs which indicates the existence of the prophecies of the prophets.